Utilization of a Coffee Peeler Machine for Coffee Farmer Groups in Gunung Tua Village Mandailing Natal: Coffee Peeler Machine - Sitorus, Tulus Burhanuddin; Nasution, Ahmad Y; Hamsi, Alfian; Lubis, Syaifuddin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Topographically, the Mandailing Natal district is divided into lowland areas which are coastal areas with an elevation of 00 -20 covering an area of ​​160,500 Ha (24.24%). One of the drivers of economic growth in Mandailing Natal district is plantations. Plantation plants in the Mandailing Natal district can develop coffee, cinnamon, coconut, candlenut, sugar palm, and cloves. However, the level of absorption of agricultural technology is still not as expected, especially for coffee farmers in Gunung Tua village, Mandailing Natal Regency, making coffee productivity from this area less than optimal. From the survey results and discussions with coffee farmer partners in the town of Gunung Tua Mandailing Natal, it was found that there were several problems in the post-harvest process, and one of them was the peeling of the coffee bean skin. So far, most coffee farmers use a coffee peeler manually with a 20 kg/hour capacity and require quite a high operational cost. Therefore, the service implementation team and coffee farmer partners agreed to make a 100 kg/hour coffee peeler machine and an electric motor drive based on these conditions. Test data in the field shows that for a coffee peeler with a capacity of 100 kg/hour, only one liter of fuel is needed to peel 400 kg of coffee beans. This, of course, makes a significant reduction in production costs in the post-harvest process. It is hoped that this machine can work optimally to reduce the production cost of coffee peeling and increase the income of coffee farmers in the village of Gunung Tua Mandailing Natal.